Ética profesional y desempeño laboral del funcionario público en el Gobierno Regional de Loreto 2021 - López Gonzáles, David (2023)
The purpose of the investigation was to expose the relationship between professional ethics and work performance of the public official in the Regional Government of Loreto. In this sense, the study method responds to a descriptive - correlational level, in the same way the non-experimental design, the population was made up of a total of 1,200 and through systematic probabilistic sampling the sample was calculated, from which 200 workers were obtained. and they were to whom the respective surveys were applied. Therefore, it has been determined that there is a significant relationship between professional ethics and work performance corroborated by a coefficient and a significance of (r=0.810; p=0.000) - considerable positive. In the same way, for sociable attitude, it sets a coefficient and a significance of (r=0.720; p=0.000). The same for economic aptitude presents a coefficient and a significance of (r=0.672; p=0.000). While personal capacity shows a coefficient and a significance of (r=0.741; p=0.000). all these results are significantly related to job performance.